The impact of underdamping on the maximum rate of the radial pressure rise during systole (dP/dtMAX) - Michard, Frederic; Foti, Lorenzo; Villa, Gianluca; Ricci, Zaccaria; Romagnoli, Stefano (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Purpose In patients with a radial arterial catheter, underdamping of the pressure signal is common and responsible for an overestimation of systolic arterial pressure (SAP). The maximum rate of the arterial pressure rise during systole (dP/dt MAX ) has been proposed to assess left ventricular systolic function. The impact of underdamping on dP/dt MAX is likely but has never been quantified. Methods We analyzed data from 70 critically ill patients monitored with a radial catheter in whom underdamping of the arterial pressure waveform was confirmed by the Gardner’s method. Invasive SAP and dP/dt MAX were recorded at baseline and after the correction of underdamping with a resonance filter. Results With resonance filtering, SAP decreased from 159 ± 25 to 139 ± 22 mmHg ( p < 0.001) and dP/dt MAX from 2.0 ± 0.6 to 1.1 ± 0.3 mmHg/ms ( p < 0.001). The underdamping-induced overestimation of SAP (delta-SAP) ranged from 6 to 41 mmHg (mean 21 ± 9 mmHg or + 15%) and the overestimation of dP/dt MAX (delta-dP/dt MAX ) ranged from 0.2 to 2.0 mmHg/ms (mean 0.9 ± 0.4 mmHg/ms or + 84%). A significant linear relationship ( p < 0.001, r = 0.6) was observed between delta-SAP and delta-dP/dt MAX such that the higher was delta-SAP, the higher was delta-dP/dt MAX . Conclusions Radial arterial pressure underdamping has a major impact on dP/dt MAX . In case of underdamping, the overestimation of dP/dt MAX is > fivefold higher than SAP overestimation. Therefore, caution should be exercised before using radial dP/dt MAX as a marker of left ventricular systolic function. Trial registration Registered at ClinicalTrials.gov on December 22, 2021 (NCT05166993). Graphical Abstract